An Exploration of Higher Education Teacher Education programmes: : During and post-COVID-19 - Bansal, Sneh (Voices of Teachers and Teacher Educators, 2023)
The higher education system in India is one of the largest systems in the world with around 1000 universities and 50,000 colleges and institutions. These, together, cater to nearly 39 million students. The COVID-19 pandemic has significantly affected the higher education system including the teacher education institutions. India too, like many other countries had to shut down their institutions and moved unexpectedly to online teaching and learning. The teacher education programmes in India are heavily dependent on the conventional approaches to teaching-learning and less is evident about the effective integration of technology in teaching. Literature reviews indicated that researchers have not examined how well the student teachers are able to learn the course content and obtain practical knowledge about the profession in the context of teacher education. It is therefore important to explore how the student teachers cope with the learning situation during online instructions in teacher education courses, particularly in the pandemic situation when the New Education Policy (2020) has been released. The purpose of the study is to assess the degree to which pre-service teachers in teacher education programs can manage the theory and internship components of online learning during the COVID-19 epidemic. The method selected was qualitative research through an open-ended questionnaire that asked student teachers to reflect on their experience of learning in the teacher education programmes they took after all instruction went online along with the challenges they encountered which affected their learning in theory and internship component. The implications of this study for the new normal in the teacher education programmes in the post pandemic world focusing on implementation of NEP 2020 in the light of teaching, learning and assessment practices was discussed.